Graduation of the hadiths of the Book of Acquiring Acquaintances in the Rectified Livelihood for Mohammed bin Sultan Al Tamimi - Al Zuhairi, Fatima bint Mohammed (Journal of Humanities & Social Sciences, 2017)
Imam Shibani’s book is a valuable reference in work ethics and Halal earnings, as he was a pioneer in collecting related Hadith and discussing the topic. Nevertheless, the original book is no longer in existence, but we have available a summarized version by Imam Shibani’s pupil Muhammad Ibn Samaa (D 187),. This summary was titled "Muktasar Al Iktisab Fi Al Rizq Al Mustatab” In this research paper, titled "Takreej Ahadith Muktasar Al Iktisab Fi Al Rizq Al Mustatab” I intend to validate the collected Hadith, and I demonstrate by dividing it into.”, and lastlyThe conclusion and the most important findings and recommendations.